EFFECT OF ORGANIC AND MINERAL FERTILIZERS AND AGRICULTURAL SULFUR ON CONCENTRATION OF N,P AND K IN SOIL AND POTATO TUBERS - Ameer Adnan Jaafar,; Kahtan Jamal Abdulrasool, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A field experiment was carried out to investigate the effect of different levels of organic and mineral fertilizers and agricultural sulfur on availability of N,P and K in soil and their concentrations in potato tubers. The experiment was carried out in the College of Agricultural Engineering Sciences - University of Baghdad, during 2021 by adding three levels of organic fertilizer (Poultry manure) 0, 5, and 10 Mg ha-1, and their symbols were OM0, OM1, and OM2, respectively. three levels of mineral fertilizer 0, 50 and 100% of the fertilizers recommendation, their symbols were C0, C1, and C2 respectively. three levels of agricultural sulfur 0, 1000, and 2000 kg ha-1, their symbols are S0, S1, and S2 respectively. Randomize complete block design was used with factorial experiment  using three replicates. The results showed an increase in soil of available nitrogen, phosphorus and potassium with levels of organic, mineral fertilizers and agricultural sulfur. The results showed  that the treatment OM2S2C2 achieved the highest mean of 62.87, 35.62 and 313.24 mg for N,P and K kg-1 soil, respectively, compared to the control treatment OM0S0C0, which gave the lowest mean of 28.7, 9.3, 262.56 mg kg-1 soil for N,P and K, respectively. The results also showed an increase in the concentrations of nitrogen, phosphorus and potassium in potato tubers. The treatment OM2S2C2 achieved the highest mean of 1.29, 0.47, 1.56 % for N,P and K, respectively, compared to the control treatment OM0S0C0, which gave the lowest mean of 0.99, 0.25, 1.02% for N,P and K, respectively.